Amidoxime-modified poly (acrylonitrile)-grafted Cassava starch and its adsorption behavior towards copper(II) ion - Yusuf, Ja'afar (2015)
The graft copolymerization of acrylonitrile onto cassava starch using sodium persulphate (SPS) and potassium persulphate (KPS) as initiators were successfully carried out. The maximum grafting efficiency (91%) and grafted yield (274%) were attained at ratio of AN:CS 3:1 within 3 hours of reaction time at 50 The graft copolymerization of acrylonitrile onto cassava starch using sodium persulphate (SPS) and potassium persulphate (KPS) as initiators were successfully carried out. The maximum grafting efficiency (91%) and grafted yield (274%) were attained at ratio of AN:CS 3:1 within 3 hours of reaction time at 50 ℃.poly(acrylonitrile-grafted-cassava) (poly(AN-g-CS)) were then chemically modified with hydroxylamine hydrochloride (NH2OH.HCl) to convert the nitrile groups into oxime functional groups.Due to low utilization and large availability of cassava starch (CS), an attempt was made to incorporate CS onto acrylonitrile (AN) and further chemically modified to convert the nitrile groups into amidoxime functional groups to form chelating ion exchange network based on acrylonitrile as an effective adsorbent for wastewater treatment. Thepoly(AN-g-CS) and amidoxime-modified poly(AN-g-CS) were characterized by Fourier transform infrared (FT-IR) spectroscopy, scanning electron microscopy (SEM), thermal gravimetric analysis (TGA), Brauner-Emmet-Teller (BET) and X-ray diffraction (XRD). The IR spectra proved that the grafting of CS onto PAN was successful and the poly(AN-g-CS) was successfully modified with hydroxylamine hydrochloride. It was shown that the specific surface area, pore volume and average pore diameter of CS significantly increased after grafting with AN and modification with NH2OH.HCl. The influence of pH, contact time, adsorbent dosage and initial metal concentration towards adsorption of Cu(II) ions into CS, poly(AN-g-CS) and amidoxime-modified poly(AN-g-CS) onto Cu(II) ions were investigated. It was shown that the amidoxime-modified poly(AN-g-CS) exhibited higher adsorption capacity towards Cu(II) ions as compared to the CS and poly(AN-g-CS).The maximum adsorption capacities were found to be 10.12 mg.g-1, 5.28 mg.g-1 and 56.02 mg.g-1 respectively for CS, poly(AN-g-CS) and amidoxime-modified poly(AN-g-CS) respectively at pH 5. The adsorption kinetic study showed that the maximum time required for Cu(II) ions to attain saturation level was 1 hour. The removal efficiency of Cu(II) ions were compared using synthetic and real wastewater containing different metal ions. The adsorption kinetic studies proved that the adsorptions were fitted with pseudo-second order. The equilibrium data were analysed by the Langmuir and ℃.poly (acrylonitrile-grafted-cassava) (poly(AN-g-CS)) were then chemically modified with hydroxylamine hydrochloride (NH2OH.HCl) to convert the nitrile groups into oxime functional groups.Due to low utilization and large availability of cassava starch (CS), an attempt was made to incorporate CS onto acrylonitrile (AN) and further chemically modified to convert the nitrile groups into amidoxime functional groups to form chelating ion exchange network based on acrylonitrile as an effective adsorbent for wastewater treatment. Thepoly(AN-g-CS) and amidoxime-modified poly(AN-g-CS) were characterized by Fourier transform infrared (FT-IR) spectroscopy, scanning electron microscopy (SEM), thermal gravimetric analysis (TGA), Brauner-Emmet-Teller (BET) and X-ray diffraction (XRD). The IR spectra proved that the grafting of CS onto PAN was successful and the poly(AN-g-CS) was successfully modified with hydroxylamine hydrochloride. It was shown that the specific surface area, pore volume and average pore diameter of CS significantly increased after grafting with AN and modification with NH2OH.HCl. The influence of pH, contact time, adsorbent dosage and initial metal concentration towards adsorption of Cu(II) ions into CS, poly(AN-g-CS) and amidoxime-modified poly(AN-g-CS) onto Cu(II) ions were investigated. It was shown that the amidoxime-modified poly(AN-g-CS) exhibited higher adsorption capacity towards Cu(II) ions as compared to the CS and poly(AN-g-CS).The maximum adsorption capacities were found to be 10.12 mg.g-1, 5.28 mg.g-1 and 56.02 mg.g-1 respectively for CS, poly(AN-g-CS) and amidoxime-modified poly(AN-g-CS) respectively at pH 5. The adsorption kinetic study showed that the maximum time required for Cu(II) ions to attain saturation level was 1 hour. The removal efficiency of Cu(II) ions were compared using synthetic and real wastewater containing different metal ions. The adsorption kinetic studies proved that the adsorptions were fitted with pseudo-second order. The equilibrium data were analysed by the Langmuir and Freundlich isotherms models. It was found that the Langmuir model is the most favourable isotherm model compared to the Freundlich model.